Efecto de la aplicación edáfica del silicio en el control de Phytophthora capsici, en el cultivo de pimiento (Capsicum annuum) - Varas Carvajal, Ivonne Alexandra (2021)
The cultivation of Capsicum annuum L. pepper has become one of the fastest growing vegetables worldwide. This crop is in the fifth place in world production and is one of the most complete vegetables in nutritional substances. The management of the disease caused by Phytophtora capsici, has caused that most of the producers give up the production of pepper. Evaluate the effect of the edaphic application of silicon in the control of Phytophthora capsici, in the cultivation of pepper (Capsicum annuum). The experiment was carried out at the Facultad de Ciencias Agropecuarias of Universidad Técnica Estatal de Quevedo. where doses of silicon were evaluated to determine the one with the greatest control in the disease. First, the efficiency of the program compared to the visual scale was determined using a linear correlation. Then, the severity of the disease was evaluated using both evaluation methods. Additionally, yield and some agronomic variables such as plant height, number of flowers, number of harvested fruits, healthy and diseased fruits, weight of healthy and diseased fruits were evaluated through variance analysis (Tukey p <0.05). It was determined that the R2 was 0.90 and 0.97 in the correlation between Leaf Doctor and visual scale of evaluation of damage in pepper leaves and fruits respectively. It was determined that the dose of 500 kg / ha of silicon allows to reduce the presence of P. capsici in the pepper crop at the foliar level and in the fruits. However, the application of silicon does not have significant differences with the control. In the economic analysis, it was established that the application of silicon is not profitable in the pepper crop, because the yields were lower than the control (0.91 kg/ plot) and the benefit / cost ratio in the control (1.0) exceeded the treatments established in the investigation Keywords: silicon, Leaf Doctor, Phytophtora capsici.